Paradigma Harmoni: (Teori dan Praktik Hukum Bisnis Syariah) - saepuddin (Institut Agama Islam Hamzanwadi Pancor, 2023)
The contemporary business landscape has witnessed a growing interest in Sharia business law, as it provides an ethical and faith-based framework for conducting economic activities. This literature review explores the concept of a